2019
DOI: 10.1002/cmdc.201800719
|View full text |Cite
|
Sign up to set email alerts
|

TAS‐120 Cancer Target Binding: Defining Reactivity and Revealing the First Fibroblast Growth Factor Receptor 1 (FGFR1) Irreversible Structure

Abstract: 1‐[(3S)‐3‐[4‐Amino‐3‐[2‐(3,5‐dimethoxyphenyl)ethynyl]‐1H‐pyrazolo[3,4‐d]pyrimidin‐1‐yl]‐1‐pyrrolidinyl]‐2‐propen‐1‐one (TAS‐120) is an irreversible inhibitor of the fibroblast growth factor receptor (FGFR) family, and is currently under phase I/II clinical trials in patients with confirmed advanced metastatic solid tumours harbouring FGFR aberrations. This inhibitor specifically targets the P‐loop of the FGFR tyrosine kinase domain, forming a covalent adduct with a cysteine side chain of the protein. Our mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 55 publications
2
58
0
Order By: Relevance
“…Overall, the distinct structural features and binding modes of these FGFR inhibitors are in keeping with their specific activity profiles suggested by the clinical data and observed in preclinical models. A recent report defining the binding mode of TAS-120 with FGFR1 based on mass spectrometry and X-ray crystallography analyses is in line with our in silico structural modeling study (18).…”
Section: Tas-120 Overcomes Multiple Clinically Observed Fgfr Kinase Dsupporting
confidence: 86%
See 1 more Smart Citation
“…Overall, the distinct structural features and binding modes of these FGFR inhibitors are in keeping with their specific activity profiles suggested by the clinical data and observed in preclinical models. A recent report defining the binding mode of TAS-120 with FGFR1 based on mass spectrometry and X-ray crystallography analyses is in line with our in silico structural modeling study (18).…”
Section: Tas-120 Overcomes Multiple Clinically Observed Fgfr Kinase Dsupporting
confidence: 86%
“…The third-generation, irreversible FGFR inhibitor TAS-120 covalently binds to a highly conserved P-loop cysteine residue in the ATP pocket of FGFR (C492 in the FGFR2-IIIb isoform; ref. 18). TAS-120 exhibits in vitro potency at low nanomolar concentrations and high specificity against wildtype FGFR1-4 as well as against some FGFR2 kinase domain mutations (19).…”
Section: Introductionmentioning
confidence: 99%
“…The third-generation, irreversible FGFR inhibitor TAS-120 covalently binds to a highly conserved P-loop cysteine residue in the ATP pocket of FGFR (C492 in the FGFR2-IIIb isoform). 37 TAS-120 exhibits in vitro potency at low nanomolar concentrations and has high specificity against wild-type FGFR1-4 as well as against some FGFR2 kinase domain mutations. In a phase I basket study of TAS-120 in patients with refractory advanced solid tumours, TAS-120 showed an ORR of 25.0% and a disease control rate of 78.6% in 28 patients with iCCA harbouring FGFR2 fusions, including some patients who had received prior therapy with an ATP-competitive FGFR inhibitor.…”
Section: Fgfr Inhibitorsmentioning
confidence: 99%
“…On the contrary, in the case of the structures 10 (C5-C6 double bond), 53.53% present only a substituent at C6 (R 5 = H) with the following distribution referring to the total number of structures: 44.46% carbon substituent [55,56] (32.12% phenyl ring [42,57,58]), 4.70% oxygen substituent [59,60], and 1.00% nitrogen substituent [32,61]. In 7.05% of the structures there is a substituent at C5 (R 6 = H) with the following distribution referring to the total number of structures: 4.16% carbon substituent [62,63] (0.10% phenyl ring [16,56]), 0.47% oxygen substituent [56,64], and 2.39% nitrogen substituent [64,65].…”
Section: Substitution Pattern At C5 and C6mentioning
confidence: 99%
“…These compounds are subsequently converted to the desired 4-unsubstituted compound (55; R 4 = H) upon treatment with a guanidine carbonate 49 under microwave irradiation [99]. We completed our approach to totally dehydrogenated pyrido[2,3d]pyrimidin-7(8H)-ones (56)(57)(58) and (17; R 4 = H) by using several oxidation protocols [16]. The construction of the pyridopyrimidine structure from pyridone 47 usually proceeds with yields higher Only one example of the first kind of disconnection was found in SciFinder, the synthesis of compound 44 [94], an intermediate in the synthesis of pobosaibu, from pyridone 42 upon treatment with S-methylisothiourea (43) and DMF (N,N-Dimethylformamide) which provides the C4 carbon atom (yield not available) ( Figure 17).…”
Section: Synthesis From a Preformed Pyridonementioning
confidence: 99%